Planning For Instructional Resources For Science Based Subjects In Secondary Schools In Kenya: Addressing Financing Options - Odundo, Paul Amolloh; Oyier, Charles Richard (Archives of Business Research, 2018)
Instructional resources are educational inputs necessary for raising quality of education across the school system. Planning for instructional resources include setting aside money through budgetary allocation for procurement of resources. An assurance for availability and adequacy of instructional resources require defined sources of funds and standardized procedures with appropriate financial base for prudent utilization. Interaction between policy and practice in budgeting process assures efficient utilization of finance for science instructional resources in schools. The study focussed on identification of gaps within national educational policy framework on budgeting process which influence planning for science instructional resources. Specifically, determining extent to which policy framework supports budgetary allocation, financial resources, standardized procedures and financial accountability in science instructional management. The study adopted frontloading approach, a methodological process that translates (inter)national human rights standards and obligations into the budget proposals required for effective implementation in public policy. The study reviewed legal instruments, publications, reports and documentation on instructional management. Findings indicated that, domesticating ICESCR in Constitution of Kenya (2010) scanty policy guidelines on issues of quality instruction; limited specific provision for budgetary allocation for science instructional resources, as much as FDSE provide no budgetary guidelines on bridging deficits, adherence to legal provision guiding procurement procedures and accountability. The study recommends streamlining of policies to entrench framework support for implementation and monitoring and evaluation of resource allocation for quality of instruction and management.